(untitled) (BIRDEM Medical Journal, 2023)
A 63-year-old diabetic man from Sherpur district, presented with 20-day history of fever and productive cough without any haemoptysis. Initially he was diagnosed as having pneumonia caused by Klebsiella pneumoniae and had been receiving sensitive antibiotic without satisfactory improvement. Clinical evaluation later revealed that, he was febrile, tachycardic, tachypneic and anaemic. Chest examination findings were consistent with consolidation at right upper chest. Further diagnostic work-up confirmed pneumonia due to co-infection by Klebsiella pneumoniae and Burkholderia pseudomallei. He tested positive for SARS-CoV-2 infection. Antibiotic was revised and his response to treatment was satisfactory till the latest follow-up. This case is reported to stress the importance for searching causes for non-resolution of pneumonia. BIRDEM Med J 2023; 13(3): 152-154